Relation of Epicardial Fat Thickness to the Severity of Heart Failure in Patients with Nonischemic Dilated Cardiomyopathy. Issue 5 (24th November 2014) - Tabakci, Mehmet Mustafa; Durmuş, Halil İbrahim; Avci, Anil; Toprak, Cuneyt; Demir, Serdar; Arslantaş, Uğur; Cerşit, Sinan; Fidan, Serdar; Kulahçioğlu, Şeyhmus; Batgerel, Ulaankhuu; Kargin, Ramazan
Abstract : Background: The aim of this study was to assess whether epicardial fat thickness (EFT) is associated with the severity of heart failure in patients with nonischemic dilated cardiomyopathy (NICMP). Methods: The study group was composed of 93 patients with NICMP and38 age‐ and sex‐matched healty individuals as the control group. The EFT was identified during end‐systole at the point on the free wall of the right ventricle. Results: Patients with NICMP had significantly lower mean EFT than those in the control group (4.1 ± 0.8 vs. 6.1 ± 1.8 mm, P < 0.001). EFT was thinnest in patients with New York Heart Association (NYHA) functional class III or IV (3.5 ± 0.5, P < 0.001). There was a significant correlation between EFT, left ventricle EF (r = 0.540 P < 0.001), and B‐type natriuretic peptide (BNP) (r = −0.695, P < 0.001) values in patients with NICMP. In addition, when EFT was corrected for BMI, EFT/BMI was lower in patients with NYHA functional class III–IV than patients with NYHA class I–II and control group (0.13 ± 0.01, 0.16 ± 0.02, 0.23 ± 0.04, respectively; P < 0.001). There was a significant correlation between EFT/BMI, left ventricle EF (r = 0.489, P < 0.001), and BNP (r = −0.549, P < 0.001) in patients with NICMP. In multivariate regression analysis, EFT (P = 0.009), BNP (P = 0.039), and left atrium volume index (P = 0.039) were independently associated with impaired functional status. Conclusion: Echocardiographic EFT is an inexpensive, simple, and readily available marker that may be used to asses the severity of chronic heart failure in patients with NICMP.